Vertex form of a parabola: y= a(x-h)^2 + k
vertex = (h,k) = (0,5)
Replacing:
y= a(x)^2 + 5
We have to solve for:
0 = ax^2 + bx + c
a = a
b= 0
c = 5
Apply the quadratic formula:
![(-b\pm√(b^2-4* a* c))/(2* a)](https://img.qammunity.org/2023/formulas/mathematics/college/ea7m0eu9n9p39zlm62qm1zvg14qinxk92i.png)
Replacing:
![(0\pm√(0-4* a*5))/(2* a)](https://img.qammunity.org/2023/formulas/mathematics/college/qt2xop5t0m204mwzs4s3xau0dklz49o8or.png)
![(√(-20a))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/k28wsr04fdulka7vl8z2cwxxovtp0mqr8p.png)
a must be negatve
Since there is a negative number under the root there is no real solution.
Answer: ∅